Composition for forming adhesive layer, laminate, method for producing laminate, and method for treating laminate

By developing a follower layer composition containing a specific compound, the problems of difficulty in laser peeling of 355nm and poor i-line development in the prior art were solved, and compatibility between 355nm laser peeling and i-line photohardening was achieved, reducing operating costs and improving the The processing efficiency of the laminated body is achieved.

CN119193074APending Publication Date: 2024-12-27NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410827298.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-06-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The adhesion composition used in the conventional LLO process is difficult to peel off the adhesion body by 355 nm laser, and the i-ray photohardening and developing properties are poor, resulting in high operating costs and inconvenient use of the adhesion layer.

Method used

A follower layer composition containing a specific compound was developed, a hardened film was formed by heat treatment, and peeled off with a 355 nm laser, while optimizing the absorption of the i-line without hindering the i-line photohardening reaction. The composition includes specific compounds, unsaturated polymerizable compounds, solvents and initiators to ensure good development of the hardened film to the high penetration rate of the 355nm laser and i-ray photocuring.

Benefits of technology

The effect of easily peeling off the attached body by a 355nm laser is achieved, while maintaining the development and subsequent strength of the i-line photohardening reaction, reducing the operating cost and improving the processing efficiency of the laminated body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004910892190000031
    Figure BDA0004910892190000031
  • Figure BDA0004910892190000032
    Figure BDA0004910892190000032
  • Figure BDA0004910892190000041
    Figure BDA0004910892190000041
Patent Text Reader

Abstract

The invention relates to a composition for forming an adhesive layer, a laminate, a method for manufacturing the laminate, and a method for processing the laminate. The present invention addresses the problem of providing a composition for forming an adhesive layer, in which (I) an adherend is easily peeled off by irradiation with 355 nm laser light after a cured film is formed by heat treatment, and (II) a photocuring reaction is satisfactorily performed without hindering the i-line (365 nm) absorption of an initiator with respect to a coating film before heat treatment. The means for solving this problem is to provide a composition for forming an adhesive layer for forming an adhesive layer that adheres a support and an adherend to each other and is capable of separating the support and the adherend by irradiation with light. The adhesive layer-forming composition contains (A) a compound that changes in absorption before and after heat treatment, (B) a polymerizable compound containing an unsaturated group, (D) a solvent, and (E) an initiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive layer-forming composition, a laminate, a method for producing a laminate, and a method for treating a laminate. Background Art

[0002] In recent years, as digital devices have become more advanced in functionality, the thinning of flexible displays and semiconductor chips mounted thereon has been progressing. However, since the strength of flexible displays and semiconductor chips has been reduced due to the thinning, it is difficult to transport them using conventional automatic transport.

[0003] Therefore, methods for safely and easily transporting thinned flexible displays and semiconductor chips are being reviewed. For example, the following method is being explored: a laminated body is made on a light-transmissive support such as a glass substrate, to which adherends such as flexible displays and semiconductor chips are fixed via an adhesive layer, and the flexible displays and semiconductor chips are transported together with the laminated body. At this time, an adhesive layer that deteriorates or decomposes and reduces the bonding strength when irradiated with light is sometimes used as the adhesive layer. If the adhesive layer is used, light can be irradiated from the side of the support to the adhesive layer after transportation, thereby separating (peeling off) the adherend from the support and, for example, transferring it to another substrate (laser lift-off process (laserlift-off process, hereinafter also referred to as "LLO process").

[0004] Regarding an adhesive composition that can be used in an LLO process, a composition obtained by dissolving a resin having a benzotriazole structure in a solvent is described in Patent Document 1. Patent Document 1 describes that an adhesive layer formed by applying the composition on a glass support and heating the composition can be easily peeled off the glass support from the adherend by irradiating the glass support with a laser having a wavelength of 355 nm.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-106486. Summary of the invention

[0008] [Problems to be solved by the invention]

[0009] In the past, the development of adhesives used in the LLO process was centered on the composition of the bonded body that can be peeled off by short-wavelength lasers (wavelengths of 248nm and 266nm, etc.) with high energy and excellent processability. However, in order to separate the bonded body with lasers of these wavelengths, it is necessary to use a support made of expensive materials such as quartz glass or sapphire substrates with high permeability in the short wavelength region. Therefore, the previous LLO process has the problem of increased operating costs. Therefore, in order to use cheaper transparent glass, it is required to develop an adhesive layer that can be peeled off the bonded body by lasers of longer wavelengths (such as 355nm, etc.).

[0010] However, conventionally known adhesive compositions are photocured by i-ray (365 nm), and although they have good developability during pattern formation, they have high transmittance at 355 nm after curing, making it difficult to peel off the adherend by irradiating 355 nm laser.

[0011] Patent Document 1 describes a composition that uses a polymer having a light-absorbing structure such as a benzotriazole structure in a repeating unit, whereby an adherend can be peeled off by irradiating a 355nm laser. However, according to the inventors, the composition has a large absorption of i-ray (365nm), so it is difficult to photoharden, and has a problem of poor developability when using i-ray.

[0012] The present invention has been studied in view of the above-mentioned point, and an object of the present invention is to provide a composition for forming an adhesive layer having the following two properties, a laminate formed by bonding a support and an adherend using the composition for forming an adhesive layer, and a method for producing and treating the laminate.

[0013] (I) After forming a cured film by heat treatment, the adherend can be easily peeled off by irradiating a 355 nm laser.

[0014] (II) The coating film before the heat treatment has low absorption of the i-line (365 nm), and the photocuring reaction proceeds well without inhibiting the absorption of the i-line (365 nm) by the initiator.

[0015] [Methods to solve the problem]

[0016] The above-mentioned problems can be solved by the following configuration.

[0017] [1] A composition for forming an adhesive layer, for forming an adhesive layer, wherein the adhesive layer is bonded to a support and an adherend, and the support and the adherend can be separated by irradiation with light,

[0018] The adhesive layer-forming composition contains:

[0019] (A) a compound represented by the following general formula (1) or (2);

[0020] (B) a polymerizable compound containing an unsaturated group;

[0021] (D) solvent; and

[0022] (E) Initiator.

[0023]

[0024] (In formula (1), Ar 1 are independently aromatic hydrocarbon groups having 6 to 14 carbon atoms, constituting Ar 1 A portion of the hydrogen atoms in the alkyl group may be substituted with a substituent selected from an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group. 2 For the 2 The carbon atom to which it is bonded and R 3 The bonded carbon atoms together form a divalent radical of the aromatic ring of the 3-benzoxazine structure. 1 R represents a single bond, -O-, -S-, -C(=O)-, -S(=O)-, -SO2-, or a divalent hydrocarbon group having 1 to 20 carbon atoms, and the aforementioned hydrocarbon group may also contain an aromatic ring. 2 and R 3 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms)

[0025]

[0026] (In formula (2), Ar 3 For the 5 The carbon atom to which it is bonded and R 7 The bonded carbon atoms together form a trivalent radical of the aromatic ring of the 3-benzoxazine structure. 4 R represents a single bond, -O-, -S-, -C(=O)-, -S(=O)-, -SO2-, or a divalent hydrocarbon group having 1 to 20 carbon atoms, and the aforementioned hydrocarbon group may also contain an aromatic ring. 5 and R 7 R each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms. 6 independently represent a hydrocarbon group having 1 to 3 carbon atoms, constituting R 6 A portion of the hydrogen atoms of the amine group may be substituted by a substituent selected from the group consisting of a thiol group, a hydroxyl group, an amine group, a SiH3 group and a vinyl group)

[0027] [2] The adhesive layer-forming composition according to [1], wherein the unsaturated group-containing polymerizable compound (B) contains:

[0028] (B1) an alkali-soluble resin containing an unsaturated group; and

[0029] (B2) An unsaturated group-containing polymerizable compound having no alkali-soluble group and having two or more ethylenically unsaturated bonds.

[0030] [3] The adhesive layer-forming composition according to [2], wherein the weight average molecular weight of the unsaturated group-containing alkali-soluble resin (B1) is 1,000 to 40,000.

[0031] [4] The adhesive layer-forming composition according to any one of [2] to [3], wherein the unsaturated group-containing alkali-soluble resin (B1) is a resin represented by the following general formula (3).

[0032]

[0033] In formula (3), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the hydrogen atoms constituting Ar may be substituted by a substituent selected from the group consisting of an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group. 8 (i) each of the following is an alkylene group having 2 to 4 carbon atoms; (ii) each of the following is an alkylene group having 2 to 4 carbon atoms; (iii) each of the following is an alkylene group having 2 to 4 carbon atoms; (iv) each of the following is an alkylene group having 2 to 4 carbon atoms; (v) each of the following is an alkylene group having 2 to 4 carbon atoms; (vi ...

[0034]

[0035] (In formula (4) and (5), R 9 are independently a hydrogen atom or a methyl group, R 10 are independently an alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R 11 are independently a saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * represents a bonding site)

[0036]

[0037] (In formula (6), W is a divalent or trivalent carboxylic acid residue, m is 1 or 2, and * indicates a bonding site)

[0038] [5] The adhesive layer forming composition as described in [2] to [4], wherein the unsaturated group-containing polymerizable compound (B2) having two or more ethylenically unsaturated bonds is an alkylene oxide-modified or lactone-modified compound having a (meth)acryloyl group.

[0039] [6] The adhesive layer-forming composition according to any one of [1] to [5], wherein the content of the compound represented by the general formula (1) or (2) described above (A) is 5% by mass to 30% by mass relative to the total mass of the solid content.

[0040] [7] The adhesive layer-forming composition according to any one of [1] to [6], wherein the amount of the solvent is 10% by mass to 80% by mass based on the total mass ratio.

[0041] [8] A composition for forming an adhesive layer, which is applied to a substrate so that a cured film obtained by heat treatment at 90°C for 3 minutes and then at 230°C for 30 minutes has a thickness of 5.0 μm, and the coating film obtained by heat treatment at 90°C for 3 minutes has a transmittance of 55% or more at 355 nm,

[0042] Furthermore, the transmittance at 355 nm of the cured film obtained by heat-treating the coating film at 230° C. for 30 minutes was reduced by 25% or more relative to the transmittance of the coating film.

[0043] [9] A laminated body comprising:

[0044] Support body;

[0045] the body to be adhered; and

[0046] The adhesive layer is disposed between the support and the adherend, and contains a cured product of the adhesive layer-forming composition according to any one of [1] to [8].

[0047]

[10] The laminate according to [9], wherein the support has a transmittance of 70% or more for light having a wavelength of 350 nm to 450 nm.

[0048]

[11] A method for manufacturing a laminate, comprising the following steps:

[0049] A step of applying the adhesive layer-forming composition described in any one of [1] to [8] to at least one surface of a support and an adherend to form an adhesive layer; and

[0050] The step of bonding the support and the adherend via the formed adhesive layer.

[0051]

[12] A method for processing a laminate, comprising the following steps:

[0052] A step of preparing the laminated body described in [9] to

[10] ; and

[0053] A step of irradiating the adhesive layer with light to separate the support and the adherend.

[0054] [Effects of the invention]

[0055] According to the present invention, there are provided a composition for forming an adhesive layer having the following two properties, a laminate formed by bonding a support and an adherend using the composition for forming an adhesive layer, and a method for producing and treating the laminate.

[0056] (I) After forming a cured film by heat treatment, the adherend can be easily peeled off by irradiating a 355 nm laser.

[0057] (II) The coating film before the heat treatment has low absorption of the i-line (365 nm), and the photocuring reaction proceeds well without inhibiting the absorption of the i-line (365 nm) by the initiator. DETAILED DESCRIPTION

[0058] Embodiments of the present invention are described below, but the present invention is not limited to the following embodiments. In addition, in the present invention, for the content of each component, when the first decimal place is 0, the record below the decimal point may be omitted sometimes. In addition, the compounds or functional groups or structures exemplified below may only use one of the compounds or functional groups or structures exemplified, or may use multiple in combination without special instructions.

[0059] In addition, the numerical range expressed using "to" in this specification means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0060] 1. Adhesive layer forming composition

[0061] A curable adhesive layer-forming composition (hereinafter, also simply referred to as a “curable composition”) according to one embodiment of the present invention contains:

[0062] A compound represented by general formula (1) or (2);

[0063] Polymeric compounds containing unsaturated groups;

[0064] solvents; and

[0065] Initiator.

[0066] In this specification, "cured film" means a film obtained by applying a composition for forming an adhesive layer to a substrate and then heating it within a preferred temperature and time range that changes the absorption of the compound represented by the general formula (1) or (2) described later (hereinafter, also referred to as "component (A)"). In addition, "coating film" means a film obtained by applying a composition for forming an adhesive layer to a substrate and before heating it within a preferred temperature and time range that changes the absorption of the component (A) described later.

[0067] 1-1. (A) Compounds represented by formula (1) or (2)

[0068] The component is a compound whose absorption changes before and after the heat treatment. In the cured film, the component (A) absorbs the laser well and generates heat. Then, the heat causes the component (B) to deteriorate and peel off the adherend. On the other hand, in the coating film, the component (A) absorbs little at the wavelength used for exposure when forming the pattern. Therefore, it is not easy to hinder the photohardening reaction performed by the initiator.

[0069] Component (A) is a compound represented by the following general formula (1) or general formula (2), preferably a compound represented by general formula (1). By using a compound represented by general formula (1), absorption at 355 nm increases after curing, and better laser lift-off properties are exhibited.

[0070]

[0071] In formula (1), Ar 1 are independently aromatic hydrocarbon groups having 6 to 14 carbon atoms, constituting Ar 1 A portion of the hydrogen atoms in the group may be substituted with a substituent selected from an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group.

[0072] In this specification, an aromatic hydrocarbon group refers to a hydrocarbon group containing an aromatic ring structure as a cyclic structure. However, an aromatic hydrocarbon group does not need to be composed only of an aromatic ring structure, and may contain a chain hydrocarbon structure and / or an alicyclic hydrocarbon structure in part thereof. The same applies to monovalent or divalent aromatic hydrocarbon groups appearing in other places.

[0073] The aromatic hydrocarbon group having 6 to 14 carbon atoms may be phenylene groups such as 1,2-phenylene, 1,3-phenylene, and 1,4-phenylene; or alkylphenylene groups such as methylphenylene and tert-butylphenylene; or naphthylene groups such as 1,5-naphthylene; or fluorenyl groups such as 9,9-fluorenyl; or halogenated phenylene groups such as fluorophenylene, chlorophenylene, and bromophenylene; or halogenated alkylphenylene groups such as trifluoromethylphenylene. Other examples include 1-phenyl-ethane-1,1-diyl. Among these, phenylene groups are more preferred, and 1,3-phenylene groups are more preferred. From the viewpoint of good absorption of laser light in the cured film, it is more preferred that the aromatic ring is directly bonded to the N atom.

[0074] Ar 2 For the 2 The carbon atom to which it is bonded and R 3 The bonded carbon atoms together form a divalent radical of the aromatic ring of the 3-benzoxazine structure.

[0075] R 1It represents a single bond, -O-, -S-, -C(=O)-, -S(=O)-, -SO2-, or a divalent hydrocarbon group having 1 to 20 carbon atoms, and the hydrocarbon group may contain an aromatic ring. From the viewpoint of imparting appropriate toughness to the cured film, it is more preferably linked to -O- or a hydrocarbon group, and more preferably linked to -O-.

[0076] R 2 and R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms. In view of the ease of synthesis of the compound, a hydrogen atom is more preferred. Examples of the hydrocarbon group include a chain hydrocarbon group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 3 to 20 carbon atoms, and an aromatic hydrocarbon group having 6 to 20 carbon atoms.

[0077] In the present specification, a chain hydrocarbon group means a hydrocarbon group that does not contain a ring structure but consists only of a chain structure, and the chain hydrocarbon group includes both a straight-chain hydrocarbon group and a branched hydrocarbon group.

[0078] Examples of the chain hydrocarbon group having 1 to 20 carbon atoms include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, and n-octyl. The chain hydrocarbon group preferably has 1 to 10 carbon atoms, and more preferably 1 to 5 carbon atoms.

[0079] In this specification, an alicyclic hydrocarbon group refers to a hydrocarbon group containing only an alicyclic hydrocarbon structure as a cyclic structure and not containing an aromatic ring structure, and an alicyclic hydrocarbon group includes both a monocyclic hydrocarbon group and a polycyclic hydrocarbon group. However, an alicyclic hydrocarbon group does not need to be composed of only an alicyclic hydrocarbon structure, and may contain a chain structure in part thereof.

[0080] Examples of the alicyclic hydrocarbon group having 3 to 20 carbon atoms include monocyclic hydrocarbon groups such as cyclopropyl, cyclopentyl, and cyclohexyl; or polycyclic hydrocarbon groups such as norbornyl and adamantyl. The alicyclic hydrocarbon group preferably has 3 to 10 carbon atoms.

[0081]

[0082] In formula (2), Ar 3 For the 5 The carbon atom to which it is bonded and R 7 The bonded carbon atoms together form a trivalent radical of the aromatic ring of the 3-benzoxazine structure.

[0083] R 4 The above hydrocarbon groups independently represent a single bond, -O-, -S-, -C(=O)-, -S(=O)-, -SO2-, or a divalent hydrocarbon group having 1 to 20 carbon atoms, and the above hydrocarbon group may contain an aromatic ring. From the viewpoint of imparting appropriate toughness to the cured film, it is more preferred to be linked to -O- or a hydrocarbon group, and more preferably to be linked to a hydrocarbon group. The number of carbon atoms in the above hydrocarbon group is more preferably 1 to 10, and more preferably 1 to 5.

[0084] R 5 and R7 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms. In view of the ease of synthesis of the compound, a hydrogen atom is more preferred. Examples of the hydrocarbon group include a chain hydrocarbon group having 1 to 20 carbon atoms, an alicyclic hydrocarbon group having 3 to 20 carbon atoms, and an aromatic hydrocarbon group having 6 to 20 carbon atoms.

[0085] Examples of the chain hydrocarbon group having 1 to 20 carbon atoms include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, and n-octyl. The chain hydrocarbon group preferably has 1 to 10 carbon atoms, and more preferably 1 to 5 carbon atoms.

[0086] Examples of the alicyclic hydrocarbon group having 3 to 20 carbon atoms include monocyclic hydrocarbon groups such as cyclopropyl, cyclopentyl, and cyclohexyl; or polycyclic hydrocarbon groups such as norbornyl and adamantyl. The alicyclic hydrocarbon group preferably has 3 to 10 carbon atoms.

[0087] R 6 independently represent a hydrocarbon group having 1 to 3 carbon atoms, constituting R 6 A portion of the hydrogen atoms in the amine group may be substituted with a substituent selected from a thiol group, a hydroxyl group, an amine group, a SiH3 group, and a vinyl group. From the viewpoint of ease of synthesis of the compound, a hydrogen atom is more preferred.

[0088] The reason why the absorption of component (A) changes before and after the heat treatment is presumed to be as follows: the compound represented by general formula (1) or (2) has a 3-benzoxazine structure, and the heat treatment causes the 3-benzoxazine to undergo ring-opening polymerization, thereby causing a change in the conjugation length.

[0089] The heating treatment temperature for changing the absorption of component (A) is preferably 150°C to 250°C, and more preferably 180°C to 230°C. In addition, the heating treatment time is preferably 30 minutes to 120 minutes, and more preferably 30 minutes to 90 minutes. When the treatment temperature is above 150°C and the treatment time is above 30 minutes, the ring-opening polymerization is well performed, and the absorption change of component (A) occurs, so the cured film shows good laser peeling properties. When the treatment temperature is below 250°C and the treatment time is below 120 minutes, no unexpected side reactions will occur, and the coloring of the cured film or the reduction of the bonding strength can be suppressed.

[0090] The component (A) may be a compound whose absorption in the wavelength range of 250 nm to 450 nm changes before and after the heat treatment. From the viewpoint of forming an adhesive layer that can be peeled off the adherend by a laser of a longer wavelength (e.g., 355 nm), a compound whose absorption in the wavelength range of 350 nm to 450 nm increases before and after the heat treatment is more preferred.

[0091] The molecular weight of component (A) is preferably 200 or more and less than 1000. When the molecular weight is 200 or more, the volatilization of component (A) during heat treatment can be suppressed, and the cured film shows good laser peeling properties. In addition, when the molecular weight is less than 1000, the compatibility with the polymerizable compound containing an unsaturated group (B) can be improved, the uniformity of the composition for forming an adhesive layer can be improved, and the bonding strength of the coating film or the cured film can be improved.

[0092] The content of component (A) is preferably 1% to 30% by mass, and more preferably 3% to 20% by mass, relative to the total mass of the solid content in the curable composition. If the content of component (A) is 5% by mass or more, the cured film after heat treatment will show good laser peelability. In addition, if the content of component (A) is 30% by mass or less, light curing is performed well in the coating film before heat treatment.

[0093] 1-2. (B) Polymerizable compound containing an unsaturated group

[0094] The (B) unsaturated group-containing polymerizable compound (hereinafter, also simply referred to as "component (B)") is a compound having a polymerizable unsaturated group and curing by a polymerization reaction of the polymerizable unsaturated group under stimulation of heat, light, or the like.

[0095] (B) The component improves the adhesion and solvent resistance of a cured film formed by curing the curable composition to an adherend.

[0096] The component (B) may be any component as long as it can ensure adhesion to an adherend and solvent resistance, and may be a well-known polymerizable compound containing an unsaturated group such as an alkali-soluble resin or an acrylic resin.

[0097] The component (B) is roughly divided into the component (B1) which is an alkali-soluble resin containing an unsaturated group, and the component (B2) which is an unsaturated group-containing polymerizable compound having no alkali-soluble group but having two or more ethylenically unsaturated bonds. The curable composition may contain only the component (B1), only the component (B2), or both the component (B1) and the component (B2) may be used in combination.

[0098] The alkali-soluble resin containing an unsaturated group of the component (B1) (hereinafter, also referred to as "component (B1)") preferably has a polymerizable unsaturated group (preferably a (meth)acryloyl group) and an acidic group (alkali-soluble group) for exhibiting alkali solubility in one molecule, and more preferably contains both a polymerizable unsaturated group and a carboxyl group. If it is the above-mentioned resin, it can be widely used without particular limitation. The above-mentioned alkali-soluble resin has both a polymerizable unsaturated group and a carboxyl group, so when patterning of the adhesive layer-forming composition is required, it can impart excellent photohardening properties, and can impart good developability and patterning properties.

[0099] In addition, “(meth)acryloyl” is a collective name for acryloyl and methacryloyl, “(meth)acrylic acid” is a collective name for acrylic acid and methacrylic acid, and (meth)acrylate is a collective name for acrylate and methacrylate, and all mean one or both of these.

[0100] The component (B1) is preferably an alkali-soluble resin containing a polymerizable unsaturated group obtained by further reacting a "reaction product of an epoxy compound having two or more epoxy groups and (meth) acrylic acid" with a polybasic acid carboxylic acid or its anhydride. When the alkali-soluble resin is produced, a polyester is generated by the reaction of a hydroxyl group with a polybasic acid carboxylic acid, but its average degree of polymerization is preferably a low molecular weight of about 2 to 500.

[0101] The epoxy compound is more preferably an epoxy compound having two or more epoxy groups. Examples of such epoxy compounds include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds (e.g., EPPN-501H: manufactured by Nippon Kayaku Co., Ltd.), phenol aralkyl type epoxy compounds, phenol novolac compounds containing a naphthalene skeleton (e.g., NC-7000L: manufactured by Nippon Kayaku Co., Ltd.), biphenyl type epoxy compounds (e.g., JER YX4000: manufactured by Mitsubishi Chemical Co., Ltd.), naphthol aralkyl type epoxy compounds, trisphenol methane type epoxy compounds, tetraphenol ethane type epoxy compounds, glycidyl ethers of polyhydric alcohols, glycidyl esters of polycarboxylic acids, copolymers of monomers having a (meth)acryloyl group containing glycidyl (meth)acrylate as units represented by copolymers of methacrylic acid and glycidyl methacrylate, 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (e.g., celloxide 2021P: manufactured by Daicel Co., Ltd.), butanetetracarboxylic acid tetra(3,4-epoxycyclohexylmethyl) modified ε-caprolactone (e.g. EPOLEAD GT401: manufactured by Daicel Co., Ltd.), epoxy compounds having an epoxycyclohexyl group represented by HiREM-1 manufactured by Shikoku Chemical Industry Co., Ltd., multifunctional epoxy compounds having a dicyclopentadiene skeleton (e.g. HP7200 series: manufactured by DIC Co., Ltd.), 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (e.g. EHPE3150: manufactured by Daicel Co., Ltd.), epoxidized polybutadiene (e.g. NISSO-PB·JP-100: manufactured by Nippon Soda Co., Ltd.), and epoxy compounds having a polysiloxane skeleton, etc.

[0102] As the component (B1), an acrylic copolymer is also preferably used.

[0103] Examples of acrylic copolymers include: copolymers of (meth)acrylic acid, (meth)acrylic acid esters, etc., and resins having (meth)acryloyl groups and carboxyl groups. Examples of the above resins include: alkali-soluble resins containing polymerizable unsaturated groups obtained by copolymerizing (meth)acrylic acid esters containing glycidyl (meth)acrylate in a solvent, reacting the copolymer with (meth)acrylic acid, and finally reacting the copolymer with an anhydride of a dicarboxylic acid or a tricarboxylic acid. The above-mentioned copolymer can refer to: the copolymer shown in Japanese Patent Publication No. 2014-111722, which is composed of 20 to 90 mol% of repeating units of diester glycerol derived from (meth) acrylic acid esterified with terminal hydroxyl groups, and 10 to 80 mol% of repeating units derived from one or more polymerizable unsaturated compounds copolymerizable therewith, and the number average molecular weight (Mn) is 2000 to 20000 and the acid value is 35 to 120 mgKOH / g; and the alkali-soluble resin containing a polymerizable unsaturated group shown in Japanese Patent Publication No. 2018-141968, which contains units derived from (meth) acrylate compounds, and units having (meth) acryloyl groups and di- or tricarboxylic acid residues, and is a polymer with a weight average molecular weight (Mw) of 3000 to 50000 and an acid value of 30 to 200 mg / KOH.

[0104] From the viewpoint of further improving the heat resistance and solvent resistance of the cured film, the component (B1) is preferably an alkali-soluble resin having multiple aromatic rings, more preferably an alkali-soluble resin having a repeating unit containing a fluorene structure, and even more preferably an alkali-soluble resin having a repeating unit containing a bisarylfluorene skeleton. For example, the component (B1) is preferably a resin represented by the following general formula (3).

[0105]

[0106] In formula (3), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the hydrogen atoms constituting Ar may be substituted by an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. 8 are independently an alkylene group having 2 to 4 carbon atoms. l is independently a number from 0 to 3. G is independently a (meth)acryloyl group or a substituent represented by the following general formula (4) or the following general formula (5). Y is a tetravalent carboxylic acid residue. Z is independently a hydrogen atom or a substituent represented by the following general formula (6), and at least one Z is a substituent represented by the following general formula (6). n is a number having an average value of 1 to 20.

[0107]

[0108]

[0109] In formula (4) and (5), R9 is a hydrogen atom or a methyl group, R 10 is an alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R 11 It is a saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.

[0110]

[0111] In formula (6), W is a divalent or trivalent carboxylic acid residue, and m is a number of 1 or 2. * represents a bonding site.

[0112] The resin represented by the general formula (3) can be synthesized by the following method.

[0113] First, an epoxy compound (B-1) having a bisarylfluorene skeleton which may have a plurality of alkylene oxide-modified groups in one molecule and represented by the following general formula (7) (hereinafter, also referred to as "epoxy compound (B-1)") is reacted with at least one of (meth)acrylic acid, a (meth)acrylic acid derivative represented by the following general formula (8), and a (meth)acrylic acid derivative represented by the following general formula (9) to obtain a diol compound belonging to epoxy (meth)acrylate. In addition, the bisarylfluorene skeleton is preferably a bis-naphthol fluorene skeleton or a bis-phenol fluorene skeleton.

[0114]

[0115] In formula (7), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the hydrogen atoms constituting Ar may be substituted by an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. 8 is independently an alkylene group having a carbon number of 2 to 4. l is independently a number from 0 to 3.

[0116]

[0117] In formula (8) and (9), R 9 is a hydrogen atom or a methyl group, R 10 is an alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R 11 is a saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10.

[0118] The reaction of the epoxy compound (B-1) with (meth) acrylic acid or its derivatives can be carried out using a well-known method. For example, Japanese Patent Publication No. 4-355450 states that about 2 moles of (meth) acrylic acid are used for 1 mole of an epoxy compound having two epoxy groups, thereby obtaining a diol compound containing a polymerizable unsaturated group. In this embodiment, the compound obtained by the above reaction is a diol (d) containing a polymerizable unsaturated group as shown in the following general formula (10) (hereinafter, also referred to as "diol (d)").

[0119]

[0120] In formula (10), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the hydrogen atoms constituting Ar may be substituted by an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, or a halogen group. G is independently a (meth)acryloyl group, a substituent group represented by general formula (2) or general formula (3), and R 8 is independently an alkylene group having a carbon number of 2 to 4. l is independently a number from 0 to 3.

[0121]

[0122] In formula (4) and (5), R 9 is a hydrogen atom or a methyl group, R 10 is an alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R 11 It is a saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, and p is a number from 0 to 10. * indicates a bonding site.

[0123] Next, the diol (d) obtained above is reacted with a divalent to tetravalent polycarboxylic acid or its monoanhydride or dianhydride. The polycarboxylic acid or its anhydride may be used alone or in combination. The above reaction can yield an alkali-soluble resin containing an unsaturated group having a carboxyl group and a polymerizable unsaturated group in one molecule as represented by the general formula (3).

[0124] The above acid component is a polybasic acid component that can react with the hydroxyl group in the diol (d) molecule. In order to obtain the resin represented by the general formula (3), it is more preferred to use a dicarboxylic acid or a tricarboxylic acid or a monoanhydride (b) thereof, and a tetracarboxylic acid or a dianhydride (c) thereof. The carboxylic acid residue of the above acid component can be any of a saturated hydrocarbon group or an unsaturated hydrocarbon group. In addition, these carboxylic acid residues can include bonds containing hetero elements such as -O-, -S-, and a carbonyl group.

[0125] Examples of the dicarboxylic acid or tricarboxylic acid or monoanhydride thereof (b) include chain hydrocarbon dicarboxylic acids or tricarboxylic acids, alicyclic hydrocarbon dicarboxylic acids or tricarboxylic acids, aromatic hydrocarbon dicarboxylic acids or tricarboxylic acids, and monoanhydrides thereof.

[0126] Examples of the above-mentioned chain hydrocarbon dicarboxylic acids or tricarboxylic acids include succinic acid, acetylsuccinic acid, maleic acid, adipic acid, itaconic acid, azelaic acid, citramalic acid, malonic acid, glutaric acid, citric acid, tartaric acid, oxoglutaric acid, pimelic acid, sebacic acid, suberic acid, and diglycolic acid, as well as these dicarboxylic acids or tricarboxylic acids into which any substituents are introduced.

[0127] Examples of the alicyclic hydrocarbon dicarboxylic acids or tricarboxylic acids include cyclobutanedicarboxylic acid, cyclopentanedicarboxylic acid, hexahydrophthalic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, methylendomethylenetetrahydrophthalic acid, chlorobridgeic acid, hexahydrotrimellitic acid, norbornanedicarboxylic acid, and these dicarboxylic acids or tricarboxylic acids into which any substituents are introduced.

[0128] Examples of the aromatic hydrocarbon dicarboxylic acid or tricarboxylic acid include phthalic acid, isophthalic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, trimellitic acid, and the like, and these dicarboxylic acids or tricarboxylic acids into which any substituent is introduced.

[0129] Among the above-mentioned dicarboxylic acids or tricarboxylic acids, succinic acid, itaconic acid, tetrahydrophthalic acid, hexahydrotrimellitic acid, phthalic acid, and trimellitic acid are more preferred, and succinic acid, itaconic acid, and tetrahydrophthalic acid are more preferred.

[0130] It is more preferable to use the monoanhydride of the dicarboxylic acid or tricarboxylic acid.

[0131] Examples of the tetracarboxylic acid or its dianhydride (c) include chain hydrocarbon tetracarboxylic acids, alicyclic hydrocarbon tetracarboxylic acids, aromatic hydrocarbon tetracarboxylic acids, and dianhydrides thereof.

[0132] Examples of the chain hydrocarbon tetracarboxylic acid include butane tetracarboxylic acid, pentane tetracarboxylic acid, hexane tetracarboxylic acid, and these chain hydrocarbon tetracarboxylic acids into which a substituent such as an alicyclic hydrocarbon group or an unsaturated hydrocarbon group is introduced.

[0133] Examples of the alicyclic hydrocarbon tetracarboxylic acid include cyclobutanetetracarboxylic acid, cyclopentanetetracarboxylic acid, cyclohexanetetracarboxylic acid, cycloheptanetetracarboxylic acid, and norbornanetetracarboxylic acid, and alicyclic tetracarboxylic acids into which a substituent such as a chain hydrocarbon group or an unsaturated hydrocarbon group is introduced.

[0134] Examples of the aromatic hydrocarbon tetracarboxylic acid include pyromelitic acid, diphenyl ketone tetracarboxylic acid, biphenyl tetracarboxylic acid, diphenyl ether tetracarboxylic acid, diphenyl sulfone tetracarboxylic acid, naphthalene-1,4,5,8-tetracarboxylic acid, and naphthalene-2,3,6,7-tetracarboxylic acid.

[0135] Among the above-mentioned tetracarboxylic acids, biphenyltetracarboxylic acid, diphenyl ketone tetracarboxylic acid, and diphenyl ether tetracarboxylic acid are more preferred, and biphenyltetracarboxylic acid and diphenyl ether tetracarboxylic acid are more preferred.

[0136] It is more preferable to use the dianhydride of the tetracarboxylic acid.

[0137] In addition, bis-trimellitic anhydride aryl esters can be used instead of the above-mentioned tetracarboxylic acid or its acid dianhydride (c). Bis-trimellitic anhydride aryl esters refer to compounds produced by the method described in International Publication No. 2010 / 074065, for example, and are acid dianhydrides in the form of ester bonds formed by the reaction of two hydroxyl groups of an aromatic diol (naphthalene diol, biphenol, and terphenyldiol, etc.) with two molecules of carboxyl groups of trimellitic anhydride.

[0138] The reaction method of diol (d) and acid components (b) and (c) is not particularly limited, and a known method can be used. For example, Japanese Patent Application Laid-Open No. 9-325494 describes a method of reacting epoxy (meth)acrylate with tetracarboxylic dianhydride at a reaction temperature of 90 to 140°C.

[0139] At this time, it is more preferred to react so that the terminal of the compound becomes a carboxyl group and the molar ratio of epoxy (meth)acrylate (diol (d)), dicarboxylic acid or tricarboxylic acid or these acid monoanhydrides (b), and tetracarboxylic dianhydride (c) becomes (d): (b): (c) = 1.0: 0.01 to 1.0: 0.2 to 1.0.

[0140] For example, when using an acid monoanhydride (b) or an acid dianhydride (c), it is more preferred to react so that the molar ratio of the amount of the acid component [(b) / 2+(c)] to the diol (d) [[(b) / 2+(c)] / (d)] is greater than 0.5 and less than 1.0. If the above molar ratio is greater than 0.5, the increase in the amount of the unreacted component in the diol (d) containing a polymerizable unsaturated group can be suppressed, and the temporal stability of the curable composition can be improved. In addition, if the above molar ratio is less than 1.0, the terminal of the alkali-soluble resin containing an unsaturated group represented by the general formula (3) will not become an acid anhydride, so the increase in the content of the unreacted acid dianhydride can be suppressed, and the temporal stability of the curable composition can be improved. In addition, for the purpose of adjusting the acid value and molecular weight of the alkali-soluble resin containing an unsaturated group represented by the general formula (3), the molar ratio of each component of (b), (c) and (d) can be arbitrarily changed within the above range.

[0141] The synthesis of the diol (d) and the subsequent reaction of the polycarboxylic acid or its anhydride are usually carried out in a solvent and optionally using a catalyst.

[0142] Examples of the above-mentioned solvent include: cellothioic acid solvents such as ethyl cellothioic acid acetate and butyl cellothioic acid acetate; high-boiling-point ether-based or ester-based solvents such as diethylene glycol dimethyl ether, ethyl carbitol acetate, butyl carbitol acetate, and propylene glycol monomethyl ether acetate; and ketone-based solvents such as cyclohexanone and diisobutyl ketone. In addition, there are no particular restrictions on the reaction conditions such as the solvent and catalyst used, for example, it is more preferable to use a solvent having no hydroxyl group and having a boiling point higher than the reaction temperature as the reaction solvent.

[0143] The reaction of the epoxy group with the carboxyl group or the hydroxyl group is preferably carried out using a catalyst. As the catalyst, ammonium salts such as tetraethylammonium bromide and triethylbenzylammonium chloride, triphenylphosphine, and tri(2,6-dimethoxyphenyl)phosphine are described in Japanese Patent Application Laid-Open No. 9-325494.

[0144] The acid value of component (B1) is preferably 50 mgKOH / g to 200 mgKOH / g, and more preferably 60 mgKOH / g to 150 mgKOH / g. If the acid value is 50 mgKOH / g or more, it is not easy to leave residue during alkali development, and if it is 200 mgKOH / g or less, the penetration of the alkali developer will not be too fast, so stripping development can be suppressed. In addition, the acid value can be obtained by titrating with a 1 / 10N-KOH aqueous solution using a potentiometric titration device "COM-1600" (manufactured by Hiranuma Industry Co., Ltd.).

[0145] The weight average molecular weight (Mw) of component (B1) measured by gel permeation chromatography (GPC) (HLC-8220GPC, manufactured by TOSOH Co., Ltd.) in terms of polystyrene is preferably 1000 to 40000, more preferably 1500 to 30000, and even more preferably 2000 to 15000. If the weight average molecular weight (Mw) is 1000 or more, the adhesion between the support and the adherend can be improved. In addition, if the weight average molecular weight (Mw) is 40000 or less, it is easy to adjust the solution viscosity of the curable composition suitable for coating, and the coating on the surface of the support or the adherend will not be too time-consuming, and it is easy to further improve the adhesion to the adherend. When the bonding strength is emphasized, the weight average molecular weight (Mw) is preferably 1000 to 4500.

[0146] The unsaturated group-containing polymerizable compound having two or more ethylenically unsaturated bonds of the component (B2) (hereinafter also referred to as "component (B2)") is a compound having two or more ethylenically unsaturated bonds and having no alkali-soluble group that undergoes polymerization reaction by stimulation of heat, light, etc.

[0147] The (B2) component can improve the bonding strength and solvent resistance of the cured film formed by curing the curable composition to the adherend. The (B2) component can be used as long as it has two or more polymerizable unsaturated groups that can react (polymerize) with "the polymerizable unsaturated group possessed by the (B1) component, or the polymerizable unsaturated group possessed by the molecules of other (B2) components". When the above-mentioned polymerizable unsaturated group is used in combination with the (B1) component, it is more preferably a functional group that is the same as the polymerizable unsaturated group possessed by the (B1) component. Specifically, the above-mentioned polymerizable unsaturated group is more preferably a (meth)acryloyl group. In addition, the (B2) component can be a monomer, or it can be an oligomer or a polymer. When used in combination with the (B1) component, the (B2) component is more preferably a monomer or an oligomer.

[0148] Examples of the (B2) component include:

[0149] (Meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tetramethylene glycol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, sorbitol penta(meth)acrylate, sorbitol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate;

[0150] Amine acrylate monomers such as pentaerythritol triacrylate toluene diisocyanate amine prepolymer, pentaerythritol triacrylate hexamethylene isocyanate amine prepolymer, pentaerythritol triacrylate isophorone diisocyanate amine prepolymer, and dipentaerythritol pentaacrylate hexamethylene diisocyanate amine prepolymer;

[0151] Epoxy (meth)acrylates such as bisphenol A epoxy (meth)acrylate, bisphenol F epoxy (meth)acrylate, bisphenol fluorene epoxy (meth)acrylate, diphenylfluorene epoxy (meth)acrylate, phenol novolac epoxy (meth)acrylate, cresol novolac epoxy (meth)acrylate, and phenol aralkyl epoxy (meth)acrylate; and

[0152] As a compound having an ethylenic double bond, a dendrimer having a (meth)acryloyl group, etc.

[0153] The component (B2) preferably has two or more (meth)acryloyl groups, and more preferably has three or more (meth)acryloyl groups. The component (B2) has two or more (meth)acryloyl groups to increase the crosslinking density and improve the solvent resistance of the coating film or cured film.

[0154] The acrylic acid equivalent of component (B2) is preferably 50 g / eq or more and 500 g / eq or less, and more preferably 70 g / eq or more and 400 g / eq or less. If the acrylic acid equivalent of the photopolymerizable compound is 500 g / eq or less, the sensitivity to radiation (such as ultraviolet rays) is high. In addition, the crosslinking density is increased, so the solvent resistance is better. If the acrylic acid equivalent is 50 g / eq or more, the crosslinking density will not become too high, and the laser stripping property will be better. In addition, the acrylic acid equivalent of the photopolymerizable compound can be obtained, for example, by dividing the molecular weight by the number of acrylic acid functional groups. In addition, the weight average molecular weight (Mw) of the photopolymerizable compound can be obtained, for example, using the above-mentioned gel permeation chromatography (GPC) "HLC-8220GPC".

[0155] From the perspective of further improving the adhesion of the cured film to the adherend, the (B2) component is preferably a compound modified by alkylene oxide or lactone. It is recognized that these modified substances improve the fluidity of the curable composition at the interface with the adherend, fill the tiny gap between the adherend and the curable composition and increase the contact area (adhesion area), thereby further improving the adhesion of the cured film to the adherend. In particular, when the (B) component is a high molecular weight compound, the (B2) component of the above-mentioned modified substance will compensate for the decrease in the fluidity of the curable composition caused by the (B) component, thereby making the above-mentioned adhesion improvement effect more significant.

[0156] The above-mentioned alkylene oxide-modified product is preferably a compound having an alkylene oxide group having 2 to 6 carbon atoms, more preferably a compound having an alkylene oxide group having 2 to 4 carbon atoms, and even more preferably a compound having an alkylene oxide group having 2 to 3 carbon atoms.

[0157] The above-mentioned alkylene oxide modified material is preferably a compound formed by adding 1 to 15 moles of alkylene oxide to 1 mole of the compound having multiple polymerizable unsaturated groups shown in the example of the above-mentioned (B2) component, more preferably a compound formed by adding 2 to 10 moles, and most preferably a compound formed by adding 2 to 8 moles. By adding more than 1 mole of alkylene oxide, the fluidity of the curable composition can be improved, and good bonding strength can be obtained. In addition, by setting it to less than 15 moles, the cross-linking density can be appropriately reduced while maintaining the bonding strength, so good laser stripping can be obtained. In addition, by setting it to less than 10 moles, better laser stripping can be obtained.

[0158] The lactone modified product is preferably a structure obtained by ring-opening a lactone having 2 to 6 carbon atoms (-C(=O)-(CH2) k -O-, k is a number less than the number of carbon atoms of the lactone by 1), more preferably a compound having a structure obtained by ring-opening a lactone having 4 to 6 carbon atoms, and still more preferably a compound having a structure obtained by ring-opening a lactone having 6 carbon atoms.

[0159] The lactone modified product is preferably a compound obtained by adding 1 to 15 moles of lactone to 1 mole of the compound having a plurality of polymerizable unsaturated groups as shown in the example of the component (B2), more preferably a compound obtained by adding 2 to 10 moles, and most preferably a compound obtained by adding 2 to 8 moles. The reason why the above range is more preferred is the same as the reason why the above alkylene oxide modified product is more preferred.

[0160] The modified product may be, for example, a compound represented by the following general formula (11).

[0161]

[0162] In formula (11), V is independently an alkylene oxide or a group having a structure obtained by ring-opening of a lactone. a to e are independently integers of 0 to 6, but at least one of a to e is an integer of 1 to 6. a to e are more preferably 1 or 2. R 12 To R 16 More preferably, each of R is independently (meth)acryloyl or hydroxyl. 12 To R 16 At least two of R are (meth)acryloyl groups. 12 To R 16 More preferably, all of them are (meth)acryloyl groups. T is a group selected from substituted or unsubstituted 1-4-valent hydrocarbon groups, -O- and -S-, more preferably substituted or unsubstituted 2-valent hydrocarbon groups, -O- and -S-, and more preferably -O-. q is independently 0 or 1, more preferably 0. r is an integer from 1 to 4, more preferably 2.

[0163] Examples of modified products represented by general formula (11) include: ethylene oxide modified dipentaerythritol hexaacrylate, dipentaerythritol dicaprolactone hexaacrylate, dipentaerythritol tricaprolactone hexaacrylate, dipentaerythritol hexacaprolactone hexaacrylate, dipentaerythritol polycaprolactone hexaacrylate (all manufactured by Nippon Kayaku Co., Ltd.), trimethylolpropane propylene oxide modified triacrylate, and trimethylolpropane ethylene oxide modified triacrylate (all manufactured by Toagosei Co., Ltd.).

[0164] Examples of the above-mentioned modified products other than the compound represented by general formula (11) include: bisphenol F ethylene oxide modified diacrylate, bisphenol A ethylene oxide modified diacrylate, isocyanuric acid ethylene oxide modified di- and triacrylates, diglycerol ethylene oxide modified acrylate (all manufactured by Toagosei Co., Ltd.), and phosphazene ethylene oxide modified hexa(meth)acrylate, etc.

[0165] The content of component (B) is preferably 10% to 90% by mass, more preferably 20% to 90% by mass, and more preferably 40% to 90% by mass relative to the total mass of the solid content in the curable composition. When the bonding strength is emphasized, the content of component (B) is more preferably 10% to 90% by mass. If the content of component (B) is 10% by mass or more, the adhesion of the cured film to the adherend is improved, and the cured film easily absorbs the irradiated laser (such as ultraviolet rays) and deteriorates or decomposes, so it is easier to separate the support and the adherend. In addition, if it is 90% by mass or less, the hardness (crosslinking density) of the cured adhesive layer will not become too high, so it is easy to ablate when irradiated with light, and it is not easy to produce residue.

[0166] The content of the component (B1) is preferably 30% to 80% by mass, and more preferably 40% to 70% by mass, relative to the total mass of the solid matter in the curable composition. When the content of the component (B1) is within the more preferred range, the bonding strength can be improved.

[0167] The content of component (B2) is preferably 10% to 40% by mass, and more preferably 15% to 35% by mass, relative to the total mass of the solid matter in the curable composition. When the content of component (B2) is 10% by mass or more, the developability and the bonding strength can be improved. When the content of component (B2) is 40% by mass or less, good developability can be obtained.

[0168] When the components (B1) and (B2) are used together, the content of the component (B2) in the curable composition is preferably 5 to 1000 parts by mass, more preferably 10 to 600 parts by mass, and even more preferably 20 to 300 parts by mass, based on the total mass of the component (B1) being 100 parts by mass. If the content of the component (B2) is 5 parts by mass or more, the polymerizable unsaturated groups in the resin are sufficient, so a sufficient cross-linked structure can be formed, thereby improving chemical resistance. In addition, if it is 1000 parts by mass or less, the cross-linking density of the adhesive layer after curing will not become too high, so it is easy to be eroded when irradiated with light, and it is not easy to generate residue.

[0169] When optical processability is required, the content of the component (B2) is more preferably 20 to 100 parts by mass based on 100 parts by mass of the total mass of the component (B1).

[0170] When adhesiveness at room temperature is required, it is more preferred to use the component (B2) alone or to use 100 to 1000 parts by mass of the component (B2) in combination with the component (B1) in an amount of 100 to 1000 parts by mass.

[0171] In addition, the component (B) may be a resin whose cured product obtained by the polymerization reaction of the polymerizable unsaturated group will be deteriorated or decomposed by absorbing an appropriate amount of electromagnetic waves (preferably electromagnetic waves with a wavelength in the ultraviolet region). For example, the component (B) may be a compound whose cured product obtained above will become the following resin, which contains a polymerizable unsaturated group and a repeating structure containing a conjugated π electron system such as a benzene ring, a condensed ring and a heterocyclic ring in the molecule. In addition, the benzene ring, the condensed ring and the heterocyclic ring may be substituted. For example, the component (B) may be a compound that can obtain a resin having a repeating unit containing a fluorene structure as the above-mentioned cured product, and may also be a compound that can obtain a resin having a diphenyl ketone structure, a diphenyl sulfoxide structure, a diphenyl sulfone structure, a diphenyl structure, a diphenylamine structure and a benzotriazole structure as the above-mentioned cured product.

[0172] 1-3. (C) Epoxy compounds

[0173] The (C) epoxy compound (hereinafter, also referred to as "component (C)") forms a crosslinked structure by reacting with functional groups such as hydroxyl groups or thiol groups and / or by addition polymerization of epoxy compounds to each other, thereby improving chemical resistance. In addition, component (C) can improve the adhesion between the support and the adherend by interacting with component (A).

[0174] (C) As an example of a component, the compound mentioned as a raw material of (B1) the alkali-soluble resin containing an unsaturated group can be mentioned.

[0175] Among these, bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol fluorene type epoxy compounds, phenol novolac type epoxy compounds, cresol novolac type epoxy compounds, and biphenyl type epoxy compounds are more preferred, and biphenyl type epoxy compounds are more preferred. Biphenyl type epoxy compounds have an excellent balance between the light absorption energy required for separation by irradiation with light and the patterning properties of the photosensitive resin composition during photocuring, which can increase the degree of freedom in designing the curable composition.

[0176] The epoxy equivalent of component (C) is preferably 100 g / eq to 300 g / eq, and more preferably 100 g / eq to 250 g / eq. In addition, the number average molecular weight (Mn) of the epoxy compound is preferably 100 to 5000. If the epoxy equivalent is 100 g / eq to 300 g / eq, and the number average molecular weight (Mn) is 100 to 5000, the solvent resistance of the coating or cured film can be improved. In addition, if the epoxy equivalent is less than 300 g / eq, the crosslinking density can be increased, so the bonding strength can be increased.

[0177] In the curable composition, the content of the epoxy compound is preferably 0 to 60 parts by mass, and more preferably 5 to 50 parts by mass, relative to the total mass of the solid content. If the content of the epoxy compound is 5 parts by mass or more, a sufficient cross-linked structure can be formed, and the chemical resistance can be further improved. In addition, if the content of the epoxy compound is 60 parts by mass or less, the cross-linking density of the adhesive layer after curing will not become too high, so it is easy to be eroded when irradiated with light, and it is not easy to generate residue.

[0178] 1-4. (D) Solvent

[0179] The (D) solvent (hereinafter, also simply referred to as “(D) component”) dissolves or disperses the components contained in the curable composition and improves the coating properties of the curable composition on the support.

[0180] Examples of the component (D) include alcohols such as methanol, ethanol, n-propanol, isopropanol, ethylene glycol, propylene glycol, 3-methoxy-1-butanol, ethylene glycol monobutyl ether, 3-hydroxy-2-butanone, and diacetone alcohol; terpenes such as α- or β-terpineol; acetone, methyl ethyl ketone, cyclohexanone, and N-methyl-2-pyrrolidone (Methyl pyrrolidone) and other ketones; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosol, methyl cellosol, ethyl cellosol, carbitol, methyl carbitol, ethyl carbitol, butyl carbitol, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, triethylene glycol monomethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, ethyl lactate, 3-methoxybutyl acetate, 3-methoxy-3-butyl acetate, 3-methoxy-3-methyl-1-butyl acetate, cellosol acetate, ethyl cellosol acetate, butyl cellosol acetate, carbitol acetate, ethyl carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate. These can be used, dissolved, and mixed to form a curable composition in a uniform solution state.

[0181] The content of the component (D) may be changed according to the target viscosity of the curable composition, etc., but the content of the component (D) is more preferably 20% by mass to 90% by mass based on the total mass of the curable composition.

[0182] 1-5. (E) Initiator

[0183] The initiator (E) (hereinafter also referred to as "component (E)") is a photopolymerization initiator, and is a compound that generates active species such as free radicals, cations, and anions by light stimulation, and initiates a polymerization reaction. A photopolymerization initiator that generates free radicals by light irradiation is more preferred.

[0184] Examples of the photopolymerization initiator include oxime ester initiators, α-hydroxyacetophenone initiators, α-aminoacetophenone initiators, acylphosphine oxide initiators, and intramolecular hydrogen abstraction photopolymerization initiators. Among them, from the viewpoint of shortening the curing time of the curable composition, oxime ester initiators or α-aminoacetophenone initiators are more preferred, and α-aminoacetophenone initiators are more preferred. Commercially available photopolymerization initiators can be used.

[0185] Examples of the photopolymerization initiator include polymerization initiators described in paragraphs 0031 to 0042 of JP-A-2011-095716 and paragraphs 0064 to 0081 of JP-A-2015-014783.

[0186] Examples of the aminoacetophenone-based initiator include 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad 379EG, Omnirad series products are manufactured by IGM Resins BV), 2-methyl-1-(4-methylthiophenyl)-2-morpholinylpropane-1-one (trade name: Omnirad 907), and APi-307 (1-(biphenyl-4-yl)-2-methyl-2-morpholinylpropane-1-one, manufactured by Shenzhen UV-ChemTech Ltd.).

[0187] Examples of the oxime ester initiator include O-oxime ester photopolymerization initiators represented by the general formula (E-1) or the general formula (E-2).

[0188]

[0189] In formula (E-1), R 17 , R 18 Each independently represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, an arylalkyl group having 7 to 20 carbon atoms, or a heterocyclic group having 4 to 12 carbon atoms, and R 19represents an alkyl group having 1 to 15 carbon atoms, an aryl group having 6 to 18 carbon atoms, or an arylalkyl group having 7 to 20 carbon atoms. Here, the alkyl group and the aryl group may be substituted by an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkanoyl group having 1 to 10 carbon atoms, or a halogen, and the alkylene moiety may contain an unsaturated bond, an ether bond, a thioether bond, or an ester bond. In addition, the alkyl group may be any of a linear, branched, or cyclic alkyl group.

[0190]

[0191] (In formula (E-2), R 20 and R 21 Each of them is independently a linear or branched alkyl group having 1 to 10 carbon atoms, a cycloalkyl group, a cycloalkylalkyl group or an alkylcycloalkyl group having 4 to 10 carbon atoms, or a phenyl group which may be substituted by an alkyl group having 1 to 6 carbon atoms. 22 Each independently represents a linear or branched alkyl or alkenyl group having 2 to 10 carbon atoms, and a portion of the -CH2- group in the alkyl or alkenyl group may be substituted with an -O- group. 20 To R 22 A part of the hydrogen atoms in the group may be substituted by halogen atoms)

[0192] Examples of commercially available oxime ester initiators include 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(O-benzoyloxime)] (trade name: IRGACURE OXE-01, IRGACURE series, manufactured by BASF), ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(0-acetyloxime) (trade name: IRGACURE OXE-02, manufactured by BASF), [8-[5-(2,4,6-trimethylphenyl)-11-(2-ethylhexyl)-11H-benzo[a]carbazyl][2-(2,2,3,3-tetrafluoropropoxy)phenyl]methanone-(O-acetyloxime) (trade name: IRGACURE OXE-03, manufactured by BASF), 1-[4-[4-(2-benzofuranylcarbonyl)phenyl]thio]phenyl]-4-methylpentanone-1-(O-acetyl oxime) (trade name: IRGACURE XE-04, manufactured by BASF, and trade name: Lunar 6, DKSH JAPAN Co., Ltd.), 1-[4-(phenylthio)phenyl]-3-cyclopentylpropane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-305, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), 1,2-propanedione, 3-cyclohexyl-1-[9-ethyl-6-(2-furylcarbonyl)-9H-carbazole-3-yl]-, 2-(O-acetyl oxime) (trade name: TR-PBG-326, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.), and 3-cyclohexyl-1-(6-(2-(benzoyloxyimino)hexanoyl)-9-ethyl-9H-carbazole-3-yl)-propane-1,2-dione-2-(O-benzoyl oxime) (trade name: TR-PBG-391, manufactured by Changzhou Qiangli Electronic New Materials Co., Ltd.).

[0193] Other photopolymerization initiators include 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one (trade name: Omnirad 127), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (trade name: Omnirad 369), 2-hydroxy-2-methyl-1-phenyl-propane-1-one (trade name: Omnirad 1173), 1-hydroxy-cyclohexyl-phenyl-ketone (trade name: Omnirad 184), 2,2-dimethoxy-1,2-diphenylethane-1-one (trade name: Omnirad 651), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (trade name: Omnirad TPO H), and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name: Omnirad 819).

[0194] In the curable composition, when the total mass of the component (B) is 100 parts by mass, the content of the component (E) is preferably 0.1 parts by mass to 30 parts by mass, and more preferably 0.3 parts by mass to 20 parts by mass. If the content of the photopolymerization initiator is 0.1 parts by mass or more, photopolymerization can be promoted and the speed of photopolymerization can be increased. In addition, if the content of the photopolymerization initiator is 30 parts by mass or less, excessive increase in sensitivity can be suppressed, and it is not easy to produce scorching, peeling residues, etc. when irradiating light and eroding.

[0195] 1-6. Other ingredients

[0196] The curable composition may be optionally blended with a photosensitizer and a curing agent thereof, a curing accelerator, a thermal polymerization inhibitor, an antioxidant, a plasticizer, a filler, a leveling agent, a defoaming agent, a surfactant, and a coupling agent.

[0197] 1-6-1. Photosensitizer

[0198] Examples of the photosensitizer include: acetophenones such as triethanolamine, triisopropanolamine, phenylbenzene, 4,4'-bisdimethylaminophenylbenzene (Michelle's ketone), 4-phenylphenylbenzene, 4,4'-dichlorophenylbenzene, hydroxyphenylbenzene, 4,4'-diethylaminophenylbenzene, acetophenone, 2,2-diethoxyacetophenone, p-dimethylacetophenone, p-dimethylaminophenylacetophenone, dichloroacetophenone, trichloroacetophenone, and p-tert-butylacetophenone; benzoin ethers such as benzoin, benzoin methyl ether, benzoin isopropyl ether, and benzoin isobutyl ether; 2-dimethylaminoethylbenzoic acid, 4-dimethylaminobenzoic acid ethyl ester, 4-dimethylaminobenzoic acid (n-butyloxy) ethyl ester, 4-dimethylaminobenzoin benzoic acid isopentyl ester, 2-ethylhexyl 4-dimethylaminobenzoate, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated phenyl ketone, 3,3',4,4'-tetrakis(tert-butylperoxycarbonyl)phenyl ketone, and 3,3'-dimethyl-4-methoxyphenyl ketone and other phenyl ketone series, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2,4-dichlorothioxanthone and other thioxanthone series; 4,4'-bisdiethylaminophenyl ketone and other aminophenyl ketone series; 10-butyl-2-chloroacridone, 2-ethylanthraquinone, 9,10-phenanthrenequinone, and camphorquinone.

[0199] In the curable composition, when the total mass of the photopolymerization initiator is 100 parts by mass, the content of the photosensitizer is preferably 0.5 parts by mass to 400 parts by mass, and more preferably 1 parts by mass to 300 parts by mass. If the content of the photosensitizer is 0.5 parts by mass or more, the sensitivity of the photopolymerization initiator can be increased and the speed of photopolymerization can be accelerated. In addition, if the content of the photosensitizer is 400 parts by mass or less, excessive increase in sensitivity can be suppressed, and it is not easy to generate scorching, peeling residues, etc. when irradiating light and eroding.

[0200] 1-6-2. Others

[0201] Examples of the above-mentioned hardening accelerators include: tertiary amines, quaternary ammonium salts, tertiary phosphines, quaternary phosphonium salts, borates, Lewis acids, organometallic compounds, and imidazoles that help promote the hardening of epoxy resins. Examples of the above-mentioned thermal polymerization inhibitors and antioxidants include: hydroquinone, hydroquinone monomethyl ether, pyrogallol, tert-butylcatechol, phenothiazine, and hindered phenol compounds. Examples of the above-mentioned plasticizers include: dibutyl phthalate, dioctyl phthalate, and tricresyl phosphate. Examples of the above-mentioned fillers include: glass fiber, silica, mica, and alumina. Examples of the above-mentioned defoamers and leveling agents include: silicone-based, fluorine-based, and acrylic compounds. Examples of the above-mentioned surfactants include: fluorine-based surfactants and silicone-based surfactants. Examples of the coupling agent include 3-(glycidyloxy)propyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, and 3-ureidopropyltriethoxysilane.

[0202] 2. Method for manufacturing laminate

[0203] The method for manufacturing a laminate according to another embodiment of the present invention comprises: (1) applying the curable composition (adhesive layer forming composition) to at least one surface of a support and an adherend to form an adhesive layer; and (2) bonding the support and the adherend via the formed adhesive layer. Each step is described below.

[0204] [Step of forming an adhesive layer]

[0205] The step of forming the adhesive layer is a step of forming an adhesive layer containing the curable composition on at least one surface of the support and the adherend.

[0206] (Support)

[0207] The type of the support is not limited as long as an adhesive layer can be formed on the surface thereof.

[0208] In the present embodiment, the support body is preferably laser-transmissive. In particular, the support body is more preferably transmissive to light (laser) with a wavelength of 10nm to 450nm, more preferably transmissive to light (laser) with a wavelength of 100nm to 450nm, and particularly preferably transmissive to light (laser) with a wavelength of 350nm to 450nm. Examples of the support body having the above-mentioned laser-transmissive property include: glass substrates, acrylic substrates, sapphire substrates, and quartz glass substrates. However, for glass substrates and acrylic substrates, it is necessary to use a substrate having a composition with sufficient transmittance of the wavelength of the light used. Among the above-mentioned support bodies, a glass substrate is more preferably used in terms of cheapness.

[0209] The support preferably has a transmittance of 70% or more for light of wavelengths of 350 nm to 450 nm in the entire wavelength range. A support having such a transmittance can sufficiently allow long-wavelength laser light (e.g., 355 nm) irradiated from the support side to pass through and reach the adhesive layer.

[0210] The above-mentioned transmittance is a value measured using an ultraviolet visible infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Co., Ltd.) with the transmittance of a single quartz glass as a base line.

[0211] (Adhesion)

[0212] Examples of the adherend include light-emitting elements such as μLEDs, semiconductor wafers, semiconductor chips, optical glass wafers, metal foils, polishing pads, resin coatings, and wiring layers.

[0213] (Adhesive layer)

[0214] The curable composition is applied to at least one surface of the support and the adherend to form an adhesive layer. The cured film after the curable composition is cured will fully absorb long-wavelength lasers (such as 355nm, etc.). Therefore, even by irradiating long-wavelength lasers, the adherend can be fully eroded and easily peeled off (excellent laser processability).

[0215] Examples of the method for applying the adhesive include well-known solution dipping method, spin coating method, ink jet method, spray method, and methods using a roll coater, land coater, slit coater, and spinner.

[0216] After the adhesive is applied by the above-mentioned application method, the solvent is dried (prebaked) to form an adhesive layer. In addition, the prebaking can be performed by heating in an oven, a hot plate, etc. The heating temperature and heating time in the prebaking can be appropriately selected according to the solvent used, for example, at a temperature of 60 to 110° C. for 1 to 10 minutes.

[0217] The thickness of the adhesive layer can be selected arbitrarily. In the present embodiment, the thickness of the adhesive layer is preferably 0.1 μm to 50 μm, and more preferably 0.5 μm to 30 μm. If the thickness of the adhesive layer is 0.1 μm or more, the adhesive layer can have sufficient holding power to adhere to the adherend. In addition, if it is 50 μm or less, the adhesive layer can be sufficiently cured by light or heat curing.

[0218] In addition, in this step, after applying the adhesive to the surface of either or both of the support and the adherend, an exposure step and a development step for patterning the adhesive layer may be included. Patterning the adhesive layer can form the adhesive layer only on the portion to be adhered to the adherend, thereby suppressing poor peeling or positional deviation of the adherend in the step of separating the support and the adherend (described later).

[0219] Examples of light used in the exposure step include visible light, ultraviolet light, far ultraviolet light, electron beam, X-ray, etc. The above light is preferably ultraviolet light (wavelength 250 to 400nm), and from the perspective of equipment cost, i-line (365nm) is more preferred. In addition, a developer suitable for alkali development is used in the development step. Examples of the above developer include aqueous solutions of sodium carbonate, potassium carbonate, potassium hydroxide, diethanolamine, tetramethylammonium hydroxide, etc. These developers can be appropriately selected in accordance with the characteristics of the resin layer, but a surfactant can be optionally added. The development temperature is preferably 20°C to 35°C, and a commercially available developer or ultrasonic washing machine can be used to accurately form a fine image. In addition, water washing is usually performed after alkali development. The development treatment method can be applied to shower development, spray development, immersion (dip) development, and puddle development.

[0220] [Step of bonding the support and the adherend]

[0221] The step of bonding the support and the adherend is a step of bonding the support and the adherend via the adhesive layer.

[0222] Examples of methods for bonding the support and the adherend include: a method in which an adherend (an adhesive is applied to the surface in contact with the adhesive layer) is brought into contact with the surface of the adhesive layer formed on the surface of the support and pressurized while heating. In addition, regarding the bonding conditions between the support and the adherend, the temperature during pressurization is preferably from room temperature to 200°C, and more preferably from 30°C to 150°C. The pressure during bonding is preferably from 0.01MPa to 20MPa, and more preferably from 0.03MPa to 15MPa. In addition, the adhesive layer can be optionally post-heated at a temperature of 120°C to 250°C after the pressurized hot pressing is completed. By bonding the support and the adherend under the above conditions, the adherend can be more firmly fixed to the surface of the support via the adhesive layer.

[0223] In addition, the support and the adherend can be bonded by photocuring in the above-mentioned bonding step. The method of photocuring the adhesive layer includes, for example, a method of irradiating light using a high-pressure mercury lamp. In addition, regarding the bonding conditions between the support and the adherend, the wavelength of the irradiated light is preferably 200nm to 500nm. The exposure amount of the irradiated light is preferably 25mJ / cm 2 Up to 3000mJ / cm 2 , more preferably 50 mJ / cm 2 Up to 2000mJ / cm 2 .

[0224] The heating during the bonding of the support and the adherend, or the post-heating of the adhesive layer in the bonding step can also serve as a heat treatment step for causing the absorption change of the component (A). That is, when the heating conditions during bonding and the post-heating conditions are within the range of the preferred heating conditions that cause the absorption change of the component (A), there is no need to set up a separate heat treatment step. When the heating conditions during bonding and the post-heating conditions are outside the range of the preferred heating conditions that cause the absorption change of the component (A), a separate heat treatment step is set after the bonding step.

[0225] As described above, a laminate is formed, which includes a support, an adherend, and an adhesive layer disposed between the support and the adherend and containing a cured product of the adhesive layer-forming composition.

[0226] 3. Method for processing laminated body

[0227] A method for treating a laminate according to one embodiment of the present invention includes: (1) preparing the laminate; and (2) irradiating the laminate with light to separate the support and the adherend. Each step is described below.

[0228] [Step of Preparing Laminated Body]

[0229] The step of preparing a laminated body is a step of forming a laminated body as described above, or preparing an already formed laminated body.

[0230] [Step of separating the support and the adherend]

[0231] The step of separating the support and the adherend is a step of separating the support and the adherend by irradiating the adhesive layer with light.

[0232] If the irradiated light can separate the support and the adherend, there is no particular limitation. In the present embodiment, the light is preferably ultraviolet light. The wavelength of the light is more preferably 10nm to 450nm, more preferably 100nm to 450nm, and particularly preferably 350nm to 450nm. If the wavelength of the light is above 10nm, the polymer of the components of the adhesive layer will deteriorate or decompose due to absorption of light, so that the strength and adhesion will be reduced, so the support and the adherend can be easily separated. In addition, if the wavelength of the light is below 450nm, the adhesive layer of the processed part will absorb light, so the generation of residues of the cured film can be suppressed. In addition, if the wavelength of the ultraviolet light is above 350nm, cheap glass substrates and acrylic substrates can be used, especially glass substrates, so the running cost can be suppressed.

[0233] Examples of the light source include a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a far-ultraviolet lamp, and a laser light source. The light source is preferably a laser light source that irradiates laser light.

[0234] Examples of the above laser include solid lasers, liquid lasers, and gas lasers. In addition, examples of the above solid laser include semiconductor excitation lasers, etc. Examples of liquid lasers include pigment lasers, etc. Examples of gas lasers include excimer lasers, etc. Among these, the above laser is preferably a semiconductor excitation laser.

[0235] Examples of the semiconductor excitation laser include Nd:YAG laser, Nd:YLF laser, Nd:glass laser, Nd:YVO4 laser, Yb:YAG laser, Yb-doped fiber laser, Er:YAG laser, Tm:YAG laser, etc. Examples of excimer laser include KrF laser, XeCl laser, ArF laser, F2 laser, etc. Among these, the laser is preferably Nd:YAG laser.

[0236] The output and cumulative light intensity of the light irradiated to the adhesive layer vary depending on the type of light source, but when the irradiated light is laser, a laser with an output of 0.1 mW to 200 W can be used. In addition, the cumulative light intensity is preferably 1 mJ / cm 2 Up to 50J / cm 2 If the accumulated light intensity is 0.1mJ / cm 2If the ion density is 50 J / cm2, it is less likely to cause scorching and peeling residues that would otherwise occur during erosion. 2 Below, the ablation rate can be appropriately controlled and processed appropriately.

[0237] When the adhesive layer is irradiated with light (laser), it is more preferred to irradiate the entire adhesive layer with laser light from the support side. The laser irradiation method is not particularly limited and can be performed by a well-known method.

[0238] This embodiment may include a step of processing the prepared laminated body before the step of separating the support body and the adherend body.

[0239] The processing methods of the above-mentioned laminate include thinning of the adherend such as dicing and back grinding, photofabrication, lamination of semiconductor chips, mounting of various elements, and resin sealing.

[0240] In addition, the present embodiment may also include a step of moving the processed stacked body from one device to another device. The method of moving the stacked body includes a method of moving the stacked body by a robot arm.

[0241] The laminated body of the present embodiment is processed as described above.

[0242] [Example]

[0243] Hereinafter, the embodiments of the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited thereto.

[0244] First, the description will be given of the synthesis examples of the unsaturated group-containing alkali-soluble resin of the component (B1). The evaluation of the resins in these synthesis examples was performed in the following manner unless otherwise specified.

[0245] In addition, when the same model is used for various measuring machines, the machine manufacturer name is omitted from the second appearance. In addition, in the examples, all glass substrates used in the production of the substrate with a cured film for measurement were subjected to the same treatment and used. In addition, when the first decimal place of the content of each component is 0, the description below the decimal point may be omitted.

[0246] [Solid content]

[0247] 1 g of the resin solution obtained in the synthesis example was impregnated into a glass filter [mass: W0 (g)] and weighed [W1 (g)]. From the mass after heating at 160° C. for 2 hours [W2 (g)], the mass was determined by the following formula.

[0248] Solid content concentration (mass %) = 100 × (W2-W0) / (W1-W0)

[0249] [Acid value]

[0250] The resin solution was dissolved in dioxane, and titrated with a 1 / 10 N-KOH aqueous solution using a potentiometric titrator "COM-1600" (manufactured by Hiranuma Sangyo Co., Ltd.).

[0251] [Molecular weight]

[0252] The weight average molecular weight (Mw) was determined by gel permeation chromatography (GPC) "HLC-8220GPC" (manufactured by TOSOH Co., Ltd., solvent: tetrahydrofuran, column: TSKgelSuper H-2000 (2 pieces) + TSKgelSuper H-3000 (1 piece) + TSKgelSuper H-4000 (1 piece) + TSKgelSuper H-5000 (1 piece) (manufactured by TOSOH Co., Ltd.), temperature: 40°C, speed: 0.6 ml / min), and the weight average molecular weight (Mw) was determined as a value converted to standard polystyrene (manufactured by TOSOH Co., Ltd., PS-Oligomer Kit).

[0253] The abbreviations described in the synthesis examples are as follows.

[0254] BPFE: bisphenol fluorene epoxy resin (an epoxy resin in which Ar in the general formula (7) is a benzene ring and l is 0, and the epoxy group equivalent is 256 g / eq)

[0255] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0256] THPA: 1,2,3,6-Tetrahydrophthalic anhydride

[0257] TPP: triphenylphosphine

[0258] AA: Acrylic acid

[0259] PGMEA: Propylene glycol monomethyl ether acetate

[0260] RUVA-93: 2-(2'-Hydroxy-5'-methacryloyloxyethylphenyl)-2-H-benzotriazole (manufactured by Otsuka Chemical Co., Ltd.)

[0261] MMA: Methyl Methacrylate

[0262] MA: Methacrylic acid

[0263] HEMA: 2-Hydroxyethyl Methacrylate

[0264] ADVN: 2,2'-azobis(2,4-dimethylvaleronitrile)

[0265] MOI: 2-isocyanatoethyl methacrylate

[0266] [Synthesis example 1]

[0267] In a reactor equipped with a temperature controller, a stirrer, a reflux cooler, and a nitrogen inlet pipe, PGMEA (233 parts by mass) as a solvent, RUVA-93 (59 parts by mass, 0.18 mol) as an unsaturated monomer containing a UV-absorbing group, MMA (16 parts by mass, 0.16 mol) and MA (9.0 parts by mass, 0.10 mol), and HEMA (15 parts by mass, 0.12 mol) as other unsaturated monomers were added, heated to 80°C, and replaced with nitrogen. ADVN (2 parts by mass) as a polymerization initiator was added and reacted for 1 hour. Thereafter, ADVN (0.5 parts by mass) was added, heated to 90°C, and aged for 3 hours to synthesize a UV-absorbing copolymer.

[0268] MOI (18 parts by mass, 0.12 mol), a tin compound (0.01 parts by mass) as a catalyst, and methoquinone (0.04 parts by mass) as a polymerization inhibitor were added thereto, and the MOI addition reaction to the ultraviolet absorbing copolymer was carried out at 60°C for about 6 hours. The end point of the reaction was confirmed by the disappearance of the isocyanate peak by FT-IR. After the reaction was completed, PGMEA was added thereto and adjusted to a solid content of 29.2% by mass to obtain a resin solution (A)'-4. The acid value (solid content conversion) of the obtained resin solution was 55 mgKOH / g, and the Mw obtained by GPC analysis was 30,000.

[0269] [Synthesis example 2]

[0270] BPFE (50.00 g, 0.10 mol), AA (14.07 g, 0.20 mol), TPP (0.26 g), and PGMEA (40.00 g) were added to a 250 mL four-necked flask equipped with a reflux cooler, and stirred at 100 to 105° C. for 12 hours to obtain a reaction product. PGMEA (25.00 g) was then added to adjust the solid content to 50% by mass.

[0271] Then, BPDA (14.37 g, 0.05 mol) and THPA (7.43 g, 0.05 mol) were added to the obtained reaction product, and stirred at 115 to 120° C. for 6 hours to obtain an alkali-soluble resin (B1) containing an unsaturated group. The obtained resin solution had a solid content concentration of 57.0% by mass, an acid value (solid content conversion) of 96 mgKOH / g, and an Mw of 3600 obtained by GPC analysis.

[0272] The adhesive layer-forming composition was prepared in the blending amounts (unit: mass %) described in Tables 1 and 2. The blending components used in Table 1 are as follows.

[0273] (Ultraviolet light absorber)

[0274] (A)-1: 3,4'-APE-BOZ, (1-(2H,4H,benzo[e]1,3-oxazin-3-yl)-3-(4-(2H,4H-benzo[e]1,3-yl)phenoxy)benzene), manufactured by Honshu Chemical Industry Co., Ltd., solid content concentration 100% by mass, molecular weight: 436.5)

[0275] (A)-2: BPF-MZ, (methylenebis(2-(2H-benzo[e][1,3]oxazin-3(4H)-yl)ethane-1-thiol), manufactured by Honshu Chemical Industry Co., Ltd., solid content concentration 100% by mass, molecular weight: 402.6)

[0276] (A)'-3: UVA-5080, copolymer of methacrylate (3-2H-1,2,3-benzotriazole-2-yl)-4-hydroxyphenylethyl ester and methyl methacrylate, manufactured by Shin-Nakamura Chemical Industry Co., Ltd., solid content concentration 41.0% by mass, molecular weight: 40,000 to 60,000)

[0277] (A)'-4: Resin solution obtained in Synthesis Example 1 (solid content concentration: 29.2% by mass, molecular weight: 30,000)

[0278] (A) '-5: RUVA-93, (2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2-H-benzotriazole, manufactured by Otsuka Chemical Co., Ltd., solid content concentration 100% by mass, molecular weight: 323.35)

[0279] (Polymerizable compound containing unsaturated group)

[0280] (B1): Resin solution obtained in Synthesis Example 2 (solid content 57.0 mass %)

[0281] (B2)-1: A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (DPHA, manufactured by Nippon Kayaku Co., Ltd.)

[0282] (B2)-2: ethylene oxide 6 mol addition product of trimethylolpropane triacrylate (aronix M-360, manufactured by Toagosei Co., Ltd.)

[0283] (B2)-3: Bisphenol A diacrylate ethylene oxide 10 mol addition product (NK ESTER A-BPE-10, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.)

[0284] (Epoxy resin)

[0285] (C): Tetramethylbiphenol type solid epoxy resin (jER YX4000HK, Mitsubishi Chemical Corporation, epoxy equivalent 180 g / eq).

[0286] (Solvent)

[0287] (D)-1: Propylene glycol monomethyl ether acetate (PGMEA)

[0288] (D)-2: Cyclohexanone (ANON)

[0289] (Initiator)

[0290] (E): 2-[4-(Methylthio)benzoyl]-2-(4-morpholinyl)propane ("Omnirad 907" manufactured by IGM Resins B.V., "Omnirad" is a registered trademark of the same company)

[0291] [Table 1]

[0292]

[0293] [Table 2]

[0294]

[0295] [Evaluate]

[0296] The following evaluations were performed using a coating film obtained by applying and drying the adhesive layer-forming composition or a cured film obtained by curing.

[0297] [Preparation of substrates with coatings or cured films for evaluation of transmittance and laser processability]

[0298] Each adhesive layer forming composition was applied using a spin coater to a plate irradiated with a low-pressure mercury lamp at a wavelength of 254 nm and an illumination of 1000 mJ / cm2 so that the film thickness after heat curing was 5.0 μm. 2 The coating film was prepared by pre-baking at 90°C for 3 minutes using a hot plate on a 125mm×125mm synthetic quartz glass substrate (hereinafter referred to as a "quartz glass substrate") whose surface was washed by ultraviolet rays. Then, a hot air dryer was used to heat the substrate at 230°C for 30 minutes to obtain a substrate with a cured film. In addition, the transmittance of the quartz glass substrate at a wavelength of 350nm to 450nm is more than 90% in the entire range of the above wavelengths.

[0299] The above-mentioned transmittance is a value measured using an ultraviolet-visible-infrared spectrophotometer "UH4150" (manufactured by Hitachi High-Tech Co., Ltd.) with the transmittance of a single quartz glass as a base line.

[0300] [Penetration evaluation]

[0301] The transmittance at a wavelength of 355 nm of the substrate with the coating film before full curing and the substrate with the cured film after full curing was measured using an ultraviolet visible infrared spectrophotometer “UH4150” (manufactured by Hitachi High-Tech Co., Ltd.).

[0302] [Laser processability (peelability) evaluation]

[0303] (Evaluation Method)

[0304] The cured film after the main curing was irradiated with laser light (laser wavelength: 355 nm) from the cured film side using a flash lamp-excited Nd:YAG Q-SW laser oscillator "Callisto" (manufactured by VTechnology Co., Ltd.). 2 The cured film was processed with laser energy of 1000 nm and the processed cured film was observed with an optical microscope. In addition, △ or above was considered acceptable.

[0305] (Evaluation Criteria)

[0306] ◎: Cured film at laser irradiation area at 200mJ / cm 2 The following reduction

[0307] ○: The cured film at the laser irradiation part exceeds 200mJ / cm 2 And 400mJ / cm 2 The following reduction

[0308] △: The cured film at the laser irradiated part exceeds 400mJ / cm 2 And 500mJ / cm 2 The following reduction

[0309] ×: The cured film at the laser irradiated part exceeds 500 mJ / cm 2 Not reduced.

[0310] [Preparation of a substrate with a cured film for subsequent strength evaluation]

[0311] Each adhesive layer-forming composition was applied to a glass substrate "#1737" using a spin coater so that the film thickness after heat curing was 5.0 μm, and pre-baked at 90°C for 3 minutes using a hot plate to prepare a coating film. Then, a glass substrate "#1737" cut to 2 mm × 2 mm was placed on the coating film, and heated on a hot plate at 110°C for 1 minute to temporarily adhere. Thereafter, a hot air dryer was used to formally cure (post-bake) at 230°C for 30 minutes to obtain a substrate with a cured film.

[0312] [Evaluation of Adhesion Strength (Shear Strength)]

[0313] (Evaluation Method)

[0314] The glass substrate "#1737" of 2 mm x 2 mm bonded to the cured film was subjected to a bonding strength test using a bare die shear tester (manufactured by Arktech).

[0315] (Evaluation Criteria)

[0316] ◎: Adhesion strength is 25MPa or more

[0317] ○: Adhesion strength is 20 MPa or more and less than 25 MPa

[0318] △: Adhesion strength is 10 MPa or more and less than 20 MPa

[0319] ×: Adhesion strength is less than 10 MPa

[0320] [Preparation of a substrate with a cured film for developing property evaluation]

[0321] Each adhesive layer-forming composition was applied to a glass substrate "#1737" using a spin coater so that the film thickness after heat curing was 5.0 μm, and pre-baked at 90°C for 3 minutes using a hot plate to prepare a coating film. Then, a negative mask of 10 to 50 μm (5 μm scale) was placed on the coating film, and the i-line illumination was 30 mW / cm 2 High pressure mercury lamp irradiation 500mJ / cm 2 Ultraviolet rays and photohardening reaction.

[0322] Then, the exposed film was immersed in a 0.8% tetramethylammonium hydroxide aqueous solution at 23°C for the development time (break time = BT) at which the pattern begins to appear + 10 seconds, and after development treatment, it was washed with water to remove the unexposed portion of the film, and a film pattern was formed on a glass substrate. The film was formally cured (post-baked) at 230°C for 30 minutes using a hot air dryer to obtain a substrate with a cured film for development evaluation.

[0323] The following evaluation was performed using the substrate with a cured film for developing characteristic evaluation.

[0324] [Developability Evaluation]

[0325] (Evaluation Method)

[0326] The 20 μm mask pattern after the main curing (post-baking) was observed with an optical microscope. △ or more was considered acceptable.

[0327] (Evaluation Criteria)

[0328] ○: Forming a pattern

[0329] △: Part of the pattern is not formed

[0330] ×: No pattern formed

[0331] The evaluation results are shown in Tables 3 and 4.

[0332] [Table 3]

[0333]

[0334] [Table 4]

[0335]

[0336] As shown in Table 3 above, it can be confirmed that the desired effect can be obtained if the adhesive layer forming composition of the present invention is used. As shown in Tables 3 and 4, it is known that in the laminated body in which the above-mentioned adhesive layer forming composition is used in the adhesive layer, the absorption of the i-line (365nm) of the coating is small, and the absorption of the i-line (365nm) of the initiator is not hindered. It is believed that the reason is that the absorption of 365nm of the (A) component in the coating is small. In addition, it is known that after the coating is heat-treated and a cured film is formed, the processability (peelability) of the laser with a wavelength of 355nm is excellent. The main reason for the excellent laser peelability of the cured film after heat treatment is that the absorption of 355nm of the (A) component is increased by heat treatment, and as a result, the adhesive layer efficiently absorbs the light of this wavelength, and the adhesive layer is deteriorated and decomposed.

[0337] In addition, by comparing Example 3 with Example 7, it can be seen that the laser stripping property is improved by using (A)-1 represented by general formula (1) over (A)-2 represented by general formula (2). It is believed that the reason is that the conjugation length of (A)-1 is further extended after heating, the absorbance becomes higher, and the transmittance is further reduced.

[0338] In addition, from the comparison of Example 1, Example 3 and Example 4, it can be seen that in Example 3 and Example 4, where the (B2) component is a compound modified by alkylene oxide or lactone, a cured film with excellent bonding strength and laser peeling properties can be obtained. The main reason for the excellent bonding strength is that the compound with high fluidity when heated is contained, thereby improving the fluidity of the dry film during heating bonding and following the bonded body. In addition, the main reason for the excellent laser peeling properties is that the crosslinking density can be appropriately reduced while maintaining the bonding strength, so that processing is possible even with weaker laser energy.

[0339] Comparison between Example 1 and Example 2 shows that the addition of the component (C) can improve the bonding strength. This is believed to be because the interaction between the components (A) and (C) improves the adhesion between the support and the adherend.

[0340] [Industrial Applicability]

[0341] The present invention can provide a laminated body with an adhesive that can be used in the manufacture of various products, and can particularly provide a laminated body that is suitable for a process of temporarily fixing to a support such as a semiconductor wafer and processing.

Claims

1. A composition for forming an adhesive layer, for forming an adhesive layer, wherein the adhesive layer is bonded to a support and an adherend, and the support and the adherend can be separated by irradiation with light, The adhesive layer-forming composition contains: (A) a compound represented by the following general formula (1) or (2); (B) a polymerizable compound containing an unsaturated group; (D) solvent; and (E) an initiator; In formula (1), Ar 1 are independently aromatic hydrocarbon groups having 6 to 14 carbon atoms, constituting Ar 1 A portion of the hydrogen atoms in the group may be substituted by a substituent selected from an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group. 2 For the 2 The carbon atom to which it is bonded and R 3 The carbon atoms to which they are bonded together form a divalent radical of the aromatic ring of the 3-benzoxazine structure, R 1 represents a single bond, -O-, -S-, -C(=O)-, -S(=O)-, -SO2-, or a divalent hydrocarbon group having 1 to 20 carbon atoms, which may also contain an aromatic ring, and R 2 and R 3 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms; In formula (2), Ar 3 For the 5 The carbon atom to which it is bonded and R 7 The carbon atoms to which they are bonded together form a trivalent group of the aromatic ring of the 3-benzoxazine structure, R 4 represents a single bond, -O-, -S-, -C(=O)-, -S(=O)-, -SO2-, or a divalent hydrocarbon group having 1 to 20 carbon atoms, which may also contain an aromatic ring, and R 5 and R 7 Each independently represents a hydrogen atom or a hydrocarbon group having 1 to 20 carbon atoms, and R 6 independently represent a hydrocarbon group having 1 to 3 carbon atoms, constituting R 6 A portion of the hydrogen atoms of the alkyl group may be substituted with a substituent selected from the group consisting of a thiol group, a hydroxyl group, an amine group, a SiH 3 group and a vinyl group.

2. The adhesive layer-forming composition according to claim 1, wherein The aforementioned (B) unsaturated group-containing polymerizable compound includes: (B1) an alkali-soluble resin containing an unsaturated group; and (B2) An unsaturated group-containing polymerizable compound having no alkali-soluble group and having two or more ethylenically unsaturated bonds.

3. The adhesive layer-forming composition according to claim 2, wherein The weight average molecular weight of the unsaturated group-containing alkali-soluble resin (B1) is 1,000 to 40,000.

4. The adhesive layer-forming composition according to claim 2, wherein The above-mentioned (B1) alkali-soluble resin containing an unsaturated group is a resin represented by the following general formula (3): In formula (3), Ar is independently an aromatic hydrocarbon group having 6 to 14 carbon atoms, and a portion of the hydrogen atoms constituting Ar may be substituted by a substituent selected from an alkyl group having 1 to 10 carbon atoms, an aryl group or an arylalkyl group having 6 to 10 carbon atoms, a cycloalkyl group or a cycloalkylalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, and a halogen group, and R 8 are independently an alkylene group having 2 to 4 carbon atoms, l is independently a number from 0 to 3, G is independently a (meth)acryloyl group or a substituent represented by the following general formula (4) or the following general formula (5), Y is a tetravalent carboxylic acid residue, Z is independently a hydrogen atom or a substituent represented by the following general formula (6), at least one Z is a substituent represented by the following general formula (6), and n is a number with an average value of 1 to 20; In formula (4) and (5), R 9 are independently a hydrogen atom or a methyl group, R 10 are independently an alkylene group or an alkylarylene group having 2 to 10 carbon atoms, R 11 are independently a saturated or unsaturated hydrocarbon group having 2 to 20 carbon atoms, p is a number from 0 to 10, and * represents a bonding site; In formula (6), W is a divalent or trivalent carboxylic acid residue, m is a number of 1 or 2, and * represents a bonding site.

5. The adhesive layer-forming composition according to claim 2, wherein The unsaturated group-containing polymerizable compound (B2) having two or more ethylenically unsaturated bonds is an alkylene oxide-modified or lactone-modified compound having a (meth)acryloyl group.

6. The adhesive layer-forming composition according to claim 1, wherein The content of the compound represented by the above-mentioned general formula (1) or (2) (A) is 5% by mass to 30% by mass based on the total mass of the solid content.

7. The composition for forming an adhesive layer according to claim 1, wherein The amount of the solvent is 10% by mass to 80% by mass based on the total mass ratio.

8. A composition for forming an adhesive layer, which is applied to a substrate in such a manner that a cured film obtained by heating at 90°C for 3 minutes and then at 230°C for 30 minutes has a thickness of 5.0 μm, and a coating film obtained by heating at 90°C for 3 minutes has a transmittance of 55% or more at 355 nm, Furthermore, the transmittance at 355 nm of the cured film obtained by heat-treating the coating film at 230° C. for 30 minutes was reduced by 25% or more relative to the transmittance of the coating film.

9. A laminate comprising: Support body; the body to be adhered; and The adhesive layer is disposed between the support and the adherend and contains a cured product of the adhesive layer-forming composition according to any one of claims 1 to 8.

10. The laminate according to claim 9, wherein The support has a transmittance of 70% or more for light having a wavelength of 350 nm to 450 nm.

11. A method for manufacturing a laminate, comprising the following steps: A step of applying the adhesive layer-forming composition according to any one of claims 1 to 8 to at least one surface of a support and an adherend to form an adhesive layer; and The step of bonding the support and the adherend via the formed adhesive layer.

12. A method for processing a laminate, comprising the following steps: A step of preparing a laminate according to claim 9; and A step of irradiating the adhesive layer with light to separate the support and the adherend.